2023
DOI: 10.3390/ma16155428
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Ag- and Sr-Doped Hydroxyapatite Coatings for Medical Applications

Abstract: Osseointegration plays the most important role in the success of an implant. One of the applications of hydroxyapatite (HAp) is as a coating for metallic implants due to its bioactive nature, which improves osteoconduction. The purpose of this research was to assess the in vitro behavior of HAp undoped and doped with Ag and/or Sr obtained by galvanostatic pulsed electrochemical deposition. The coatings were investigated in terms of chemical bonds, contact angle and surface free energy, electrochemical behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 144 publications
1
7
0
Order By: Relevance
“…A possible explanation for these low levels of ALP activity could be represented by a faster maturation process of the pre-osteoblast grown in contact with the surface of the newly designed materials into osteocytes, cells reported in the literature as expressing low ALP activity [50]. Similar results were noticed by our group in another study [51], where HA-based coatings led to a reduction in the ALP expression levels at 14 days post seeding in comparison to the control sample (flat Ti). Moreover, Genge et al [52] observed a direct correlation between the loss in the ALP activity and the accumulation of calcium inside the matrix vesicles, a phenomenon associated with the osteogenic differentiation process.…”
Section: Osteogenic Differentiation Capacitysupporting
confidence: 86%
“…A possible explanation for these low levels of ALP activity could be represented by a faster maturation process of the pre-osteoblast grown in contact with the surface of the newly designed materials into osteocytes, cells reported in the literature as expressing low ALP activity [50]. Similar results were noticed by our group in another study [51], where HA-based coatings led to a reduction in the ALP expression levels at 14 days post seeding in comparison to the control sample (flat Ti). Moreover, Genge et al [52] observed a direct correlation between the loss in the ALP activity and the accumulation of calcium inside the matrix vesicles, a phenomenon associated with the osteogenic differentiation process.…”
Section: Osteogenic Differentiation Capacitysupporting
confidence: 86%
“…To the best of the authors' knowledge, most of the in vitro studies related to osteointegration properties of a biomaterial are still focused on the use of cell cultures in monolayer or direct and indirect co-cultures seeded onto biomaterials [24,26,[31][32][33] to evaluate the effects of tested materials or part of them on viability, morphology, gene/protein expression, and commitment; the set-up of complex tissue cultures mimicking implant osteointegration is still limited. Recently, Zankovic et al and Przekora et al performed human bone organ cultures with implanted biomaterials made of 3D-printed Ti6Al4V disks and chitosan/curdlan/hydroxyapatite for 28 and 46 days, respectively, in static conditions [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Stanic and collaborators investigated the antimicrobial activity of Ag-Hydroxyapatite against microorganisms responsible for implant-related biofilms. The AFM analysis shows the morphological changes of the fungal or bacterial cells due to Ag-Hydroxyapatite activity [ 104 ]. A more recent study investigates the nano-interactions of CuI-TiO 2 NMs and fungal cells [ 5 ].…”
Section: Atomic Force and Holotomography Microscopy In Cancer Microbi...mentioning
confidence: 99%